PENGARUH KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN DENGAN KINERJA KEUANGAN SEBAGAI VARIABEL INTERVENING - Wardani, Dini Dwi; Sa’adah, Lailatus (Fakultas Ekonomi, Program Studi Akuntansi, 2020)
This study aims to examine the effect of environmental performance as an independent variabel on firm value as the dependent variable and financial performance as an intervening variable. The population in this study are mining and the basic industrial and chemical manufacturing companies listed on the Indonesia Stock Exchange (IDX) and listed on the PROPER ranking in 2016-2018 as many 14 companies. The method used in this study is path analysis. In this study the environmental performance variable is proxied by the assessment of PROPER ratings obtained in the Ministry of Environmental website, the firm value is proxied by Tobins’Q, and for financial performance variable is proxied by return on assets (ROA). The results obtained from this study are that environmental performance has a significant effect on financial performance, environmental performance has a significant effect on firm value, financial performance has a significant effect on firm value. however, and financial performance has no effect on firm value with financial performance as an intervening variable.